Analisis Kedudukan Hukum Rekomendasi Dewan Perwakilan Rakyat Kota Pekanbaru dalam Rapat Dengar Pendapat Perspektif Kepastian Hukum - Zulwisman Zulwisman; Meri Yulia Susanti; Christin Amelia Carolina Napitupulu; Septi Marcelina Indah Ceria Ziliwu; Dirga Maulana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
This study aims to analyze the legal position of the recommendations issued by the Regional House of Representatives (DPRD) of Pekanbaru City through public hearing meetings and to examine their implementation from the perspective of legal certainty theory in relation to the implementation of regional government functions. This research employs a normative legal research method using statutory and conceptual approaches. Legal materials were obtained from laws and regulations, legal literature, scientific journals, and expert doctrines related to regional governance and legal certainty theory. The results indicate that DPRD recommendations produced in public hearing meetings constitute political and administrative supervisory instruments derived from the DPRD’s oversight function as regulated under Law Number 23 of 2014 concerning Regional Government. However, such recommendations are not included within the hierarchy of laws and regulations and therefore do not possess generally binding legal force. From the perspective of legal certainty theory, the absence of explicit regulations concerning the binding force and follow-up mechanisms of DPRD recommendations creates legal uncertainty in their implementation by regional governments.